LIBRARIES IN PROMOTING READING HABITS IN THE INTERNET ERA - Sharma, Priya (International Journal of Research -GRANTHAALAYAH, 2025)
Many activities of academic life require the ability to read and write. Reading helps to develop the mind and personality of a person; it also enriches ones’ intellectual abilities. Libraries play a leading role in the promotion of reading habits. Therefore, libraries should be well equipped with print resources as well as electronic resources to develop the reading culture among masses. In this internet era, information technology brought a drastic change in reading habits of users. The information technology influenced students’ learning in classroom as well as their reading behaviour. The challenges for students today is to acquire skills such as how to learn, how to make critical judgments, and how to communicate intelligently, to be flexible, adaptable and tolerant to other creeds and cultures and to make contributions to the society and to the well-beings of others.